LTE Coverage Network Planning and Comparison with Different Propagation Models - Rekawt Sabir Hassan; T. A. Rahman; A. Y. Abdulrahman (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
Long Term Evolution (LTE) is the next step (fourth generation) mobile radio communication technology that succeeds the HSPA.3GPP standardization body. LTE is expected to be the most competitive radio technology in the future to provide high-data-rate transmission, low latency, improved service and reduced costs. This paper focuses on one of the basic steps in the LTE network planning, by employing LTE dimensioning process, such as link budget and planning, for uplink and downlink coverage, as well as categorization of simulated received signal strengths. Also, a comparison of different propagation models, used by ATDI software (free-space, Okumura / Hata / David, Stanford University Interim (SUI), COST-231 Hata and ITU -R 525/526 Deygout). The Okumura / Hata / David’s model showed the highest received power sensitivity (-61 dBm, at 3 km separation distance), while COST-231 Hata model shows the lowest sensitivity at same distance (-96 dBm). In this paper, ATDI planning LTE radio planning software platform has been used for estimating the coverage of UTM, which is a dense urban environment.